Stem cell transplantation improves aging-related diseases - Ikehara, Susumu; Li, Ming (Frontiers in Cell and Developmental Biology, 2014)
Aging is a complex process of damage accumulation, and has been viewed as experimentally and medically intractable. The number of patients with age-associated diseases such as type 2 diabetes mellitus (T2DM), osteoporosis, Alzheimer’s disease (AD), Parkinson’s disease, atherosclerosis, and cancer has increased recently. Aging-related diseases are related to a deficiency of the immune system, which results from an aged thymus and bone marrow cells. Intra bone marrow-bone marrow transplantation (IBM-BMT) is a useful method to treat intractable diseases. This review summarizes findings that IBM-BMT can improve and treat aging-related diseases, including T2DM, osteoporosis and AD, in animal models.